2006
DOI: 10.1353/rhe.2006.0037
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Structural Diversity, Informal Peer Interactions and Perceptions of the Campus Environment

Abstract: Recent research and critiques of affirmative action in college admissions raise questions about popular approaches for enhancing learning outcomes, suggesting that a diverse student body is neither a necessary nor a sufficient condition for experiencing diversity, creating supportive learning environments, or fostering desired outcomes of college. This study found that the diversity of a student body was positively related to interactions among students from different backgrounds but not meaningfully related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 49 publications
(39 reference statements)
3
93
1
2
Order By: Relevance
“…Third, as noted previously, most studies are finding that more interactions across race/ethnicity take place in increasingly diverse environments (Chang, 1999;Chang, Astin, & Kim, 2004;Pike & Kuh, 2006); however, the quality of those cross-racial interactions during college is often determined by whether students had informal interactions with various groups before college (Sáenz, 2005;Sáenz et al, 2007). These findings about the quality of contact experiences and "perpetuation effects" in college were only made possible when researchers began to work longitudinally, assessing initial predispositions and behaviors in high school or at college entry, intergroup behaviors during college, and behaviors and beliefs after college (Jayakumar, 2007;Sáenz, 2005).…”
Section: The Behavioral Dimension Of the Climatementioning
confidence: 85%
“…Third, as noted previously, most studies are finding that more interactions across race/ethnicity take place in increasingly diverse environments (Chang, 1999;Chang, Astin, & Kim, 2004;Pike & Kuh, 2006); however, the quality of those cross-racial interactions during college is often determined by whether students had informal interactions with various groups before college (Sáenz, 2005;Sáenz et al, 2007). These findings about the quality of contact experiences and "perpetuation effects" in college were only made possible when researchers began to work longitudinally, assessing initial predispositions and behaviors in high school or at college entry, intergroup behaviors during college, and behaviors and beliefs after college (Jayakumar, 2007;Sáenz, 2005).…”
Section: The Behavioral Dimension Of the Climatementioning
confidence: 85%
“…Universities are substantially more diverse than primary and secondary schools, but diversity alone does not guarantee the development of meaningful social relationships across racial/ethnic boundaries [40,47]. Much of the existing research finds that, on college campuses, micro-level segregation is high, and that White students have the most segregated friendship networks [40,48].…”
Section: Discussionmentioning
confidence: 99%
“…Using path analytic methods on 1,343 freshmen in a highly selective private residential research I university, the authors showed that in addition to individual background characteristics, initial institutional commitment, social integration, subsequent institutional commitment, and organizational attributes (e.g., a student's opinion regarding institutional communication, fairness in policy and rule enforcement, and the ability to participate in decision making) influence not only social integration, but also intent to reenroll. Evaluating 45,000 seniors at 305 institutions in spring of 2001 using the National Survey of Student Engagement, Pike and Kuh (2006) examined the relationship among structural diversity, informal peer interactions and perceptions of the campus environment and concluded that institutional characteristics and initiatives can have direct and powerful effects on student behavior (Pike and Kuh 2006).…”
Section: Background and Literature Reviewmentioning
confidence: 99%